Analysis of the effect of PCR testing and antigen testing on controlling the transmission for Omicron based on different scenarios - Wentao Song; Buasiyamu Abudunaibi; Zeyu Zhao; Weikang Liu; Xiaolan Wang; Tianmu Chen (Infectious Disease Modelling, 2023)
After the policy adjustment, China no longer carries out COVID-19 PCR testing for all people, and antigen testing has become the main way to detect and manage infectious sources. We developed a dynamic model to evaluate and compare the effects between PCR and antigen testing for controlling the pandemic. Due to the increase of contact degree, the peak reduction effect of PCR testing in population is lower than that of antigen testing. Even if it was only 20% of people isolated at home after antigen testing, the peak of the epidemic could be reduced by 9.46%. If the proportion of antigen testing is further increased to 80%, the peak of the pandemic can be reduced by 31.41%. Antigen testing performed better effects in school (reduction proportion 29.27%) and community (29.34%) than in workplace (27.75%). Therefore, we recommend that antigen testing in the population should be encouraged during the pandemic, and home isolation of infected persons should be advocated, especially in crowded places. To improve the availability of antigen, the testing proportion should be further enhanced.